Considerações sobre a biodistribuição do 99mTc-1-TIO--D-gilcose e dosimetria em modelo animal - Andre Lima de Souza Castro (2013)
The Nuclear Medicine clinical diagnosis has been increasingly used, since it allows to evaluate physiological processes noninvasively and early detect functional abnormalities or pathologies. There is interest to develop new radiopharmaceuticals that may provide greater diagnostic specificity with minimal dose to the patient and also be available and affordable to Nuclear Medicine centers. Whenever new or experimental radiopharmaceuticals are developed, the U.S. Food and Drug Administration (FDA) recommends a dosimetric study of these radiopharmaceuticals to evaluate radiological hazards of its use. Therefore, this work aimed to study the in vivo biodistribution of the radiochemical impurities 99mTcO4-, 99mTcO2 and complex 99mTc-1-tio--D-glicose (99mTc-1-TG) in a Wistar rat and investigate the absorbed doses to animal's organs and the effective dose from the construction of a rat voxel model used in a computer simulation of the interaction of radiation with tissue. The methodology consisted of computationally modeling the biodistribution of species, from biokinetics data acquired in scintigraphic images of Wistar rats. The Monte Carlo N-Particle code used this model to simulate the interaction of radiation with tissues and the SISCODES software provided the absorbed doses in each organ according to the biodistribution of the radiopharmaceutical. The effective dose was calculated according to the recommendations of the International Commission on Radiological Protection 2007 (ICRP, 2007). The results described the biodistribution of the compounds 99mTc-1-TG, 99mTcO4- and 99mTcO2 through scintigraphic images and biokinetics curves of the percentage injected activity versus examination time. Also have described the stages involved in a voxel model construction and parameters acquirement used by the SISCODES program as weighting factor to establish the energy deposited per mass in each organ or tissue. Finally, the results presented the effective dose and absorbed doses to bladder, brain, heart, stomach / gastrointestinal tract, liver, gonads, bone, bone marrow, lungs, kidneys, thyroid, and their spatial distribution, displayed in axial and coronal images of the voxel model constructed. The obtained values of the absorbed doses and effective dose in animals were extrapolated to the standard man. For 99mTc-1-TG complex the calculated effective dose was 8.4x10-3 mSv / MBq. A typical 370MBq administration of this complex, would result in an effective dose of 3.1 mSv for the standard man. This value is below the 0.05 Sv limit established by the FDA, and also below the 7.3 mSv effective dose calculated to 18F-FDG radiotracer examination. It is concluded that the dose deposition of 99mTc-1-thio--D-glucose is lower or similar to V currently used radiopharmaceuticals in nuclear medicine and the internal dose calculation can be performed reliably and accurately using SISCODES system.